Inclusive Education Schools: A Literature Review - Danu Andiyanto; Hasan Hariri (Penerbit Goodwood, 2022)
Purpose: Optimizing inclusion programs in schools to improve teacher skills through co-teaching training and training to create an inclusive and learning-friendly environment. Methodology: This type of research uses a literature review. Results: Based on a literature review, information was obtained about several ways to optimize an inclusive environment that is good for regular students and students with special needs, such as building an excellent inclusive learning environment that requires cooperation from various parties, bringing in professionals to provide knowledge to teachers about handling students with special needs, participating in multiple pieces of training, one of which is training on co-teaching, a teaching method, namely two teachers teaching one class, and can also take part in LIRP (learning-friendly, inclusive environment) training. Limitations: Data collection techniques and articles only use a few search engines. Contribution: Based on the literature review results, providing training or professional direction to teachers regarding co-teaching is beneficial for teachers who do not have a special children's education background. Two teachers handling the class can be done effectively if the two teachers have discussed and planned to take and also learning designs suitable for students with special needs.